1990
DOI: 10.1016/0304-3959(90)91115-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of distraction on responses to cold pressor pain

Abstract: Subjective pain ratings and tolerance time were obtained during 2 cold pressor immersions for 3 groups of subjects. During the second immersion 1 group performed no task and the other 2 groups performed either an easy or difficult mental arithmetic task. The sensory-discriminative response to pain was measured by pain ratings. Pain ratings were collected every minute until subjects removed their arm from the cold pressor or until 4 min passed. Relative to a baseline cold pressor immersion, subjects in both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 7 publications
3
73
2
Order By: Relevance
“…Studies investigating this idea have manipulated the difficulty of the distraction task. However, results do not support the central role of task difficulty [23,40,47], thereby challenging the validity of the capacity models.…”
Section: Introductionmentioning
confidence: 68%
“…Studies investigating this idea have manipulated the difficulty of the distraction task. However, results do not support the central role of task difficulty [23,40,47], thereby challenging the validity of the capacity models.…”
Section: Introductionmentioning
confidence: 68%
“…We chose the cold pressor (ie immersion of a limb in ice water) because it exhibits these attributes (al'Absi and Petersen, 2003;Bullinger et al, 1984;Ehrenreich et al, 1997;Farhadi et al, 2005;Gregg et al, 1999;Lovallo, 1975) yet is difficult to ignore. In fact, the response is independent of the subjects' attentiveness (Hodes et al, 1990) and is predicted by the duration of exposure to the stimulus (Lovallo, 1975). Equally important is that data suggest that the systemic actions of the cold pressor (ie cold, elevated blood pressure) have no effect or may actually blunt HPA secretion (Edelson and Robertson, 1986;Kendler et al, 1978;Wittert et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Although distraction seems to be omnipresent in pain treatment programs for acute and chronic pain [20,41], results on its efficacy are variable. Some studies found that distraction reduces pain [36,39,44,57,58,65], whereas other studies reported no effect [25,35] or even counter-productive effects [8,21]. An understanding of the conditions under which distraction works is therefore required.…”
Section: Introductionmentioning
confidence: 99%